The Seasons of a man's life - Levinson, Daniel J. (Daniel Jacob), 1920-1994 (Knopf, 1978)
The radical new theory of adult development that shows how every grown man must pass through a series of specific age-linked phases which underlie his personal crisis, govern his emotional states and attitudes, even shape his behavior.